Celebration: Robert Spaemann’s View - Kożuchowski, Józef (Sensus Historiae, 2019)
The article presents the view of one of the most prominent contemporary German thinkers on the issues, Robert Spaemann, concerning celebration in the context of culture, worship, common good, liturgy, and beauty. Concepts such as recreation, contemplation, and meaning of life were brought up. Assuming that both religious festivals and culture are derived from religious worship, large part of the considerations concerning worship is related to the other two issues as well as to the question of the relationship between the liturgy of the Eucharist and beauty. Spaemann was the only one among the prominent thinkers of the most recent German philosophy to speak on the question of celebration (about forty years earlier this was done by Joseph Pieper), deserving recognition and gratitude. In the spirit of the classical tradition (especially Judeo-Christian), Spaemann recalled and tried to show in a somehow novel way (by taking into account the changed civilisational context) the original meaning of holidays and the significance of their celebration, especially Sundays. Therefore, at the same time, he underscored and pointed out how dramatic the repercussions can be for our civilisational identity and for us, too, if we negate holidays and not protect them by legal means. The author of the article argued that the originality of Spaemann’s approach, in comparison with Pieper’s interesting vision, is manifested, among others, in his view of worship and his emphasis on the special significance of the Eucharist as the source of our self-fulfilment, the sense of existence and uninterrupted inspiration of art creators and as the foundation of Western culture.